Protein-DNA interactions: statistical analysis of interatomic contacts in major and minor grooves - A. A. Anashkina; E. N. Kuznetsov; A. V. Batianovskii; L. A. Uroshlev; V. G. Tumanyan; N. G. Esipova (Вавиловский журнал генетики и селекции)
The interactions between protein and DNA in essence underlie all processes in a living cell. Understanding the principles of specific recognition of DNA sites will open the way to understand how these processes are controlled and to interfere in their operation. In the paper we studied contacts between the protein and DNA at the atomic level in the structures of all the 3 518 proteinDNA complexes available in PDB by the Voronoi–Delaunay tessellation method. The method unambiguously defines contacts between atoms without any parameters, and characterizes each contact by the distance between atoms and the contact area, which is determined by the corresponding face of the Voronoi polyhedron. It was shown that most contacts are formed between the protein atoms and the sugarphosphate backbone of the DNA (72.9 %). The contact with the atoms of the nucleic bases emerging into the grooves of DNA is 17.0 % for a major groove and 10.1 % for all atomic contacts for a minor groove. Totally, the interaction between protein atoms and nucleic base atoms accounts for 27.1 % of all contacts. Analysis of the accessible surface area of atoms in the major and the minor grooves showed a correlation with the number of contacts (coefficient of linear correlation 0.94 and 0.93, respectively), however, nucleic acid atoms forming hydrogen bonds make contacts more often than may be expected from statistical considerations. It was shown that conformationally stable peptides occur sometimes in the binding regions with DNA. Analysis of the residues in a predefined conformation in 3 518 proteinDNA complexes revealed 159 amino acid residues in a predefined βbend type I conformation, 15 residues in the conformation of βbend type I’, and 6 residues in the conformation of βbend type II. No residues in the conformation of βbend type II’ were found. Analysis of contacts showed that such residues virtually do not form contacts with DNA. Contacts with nucleic base atoms are found only in the two homologous structures 3qea and 3qe9, where threonine atoms form contacts with atoms of nucleotide bases of the ATpair.